SYNTACTIC ANALYSIS: WHEN WILL THE DIFFERENCE BETWEEN THEORY AND PRACTICE END? - Namozov Abdimurot (Western European Studies, 2024)
The article focuses on the linguistic analysis of sentences in the text. In particular, the process of syntactic analysis, which is one of the manifestations of linguistic analysis, focuses on aspects that need to be taken into account. methodical advice on determining the application of the sentence in three syntactic tasks - a description of the method of teaching
Keywords: Syntax; Syntactic Analysis; Parts of Speech